Empirical measurements of households' access to credit and credit constraints in developing countries: methodological issues and evidence - Diagne, Aliou; Zeller, Manfred; Sharma, Manohar (International Food Policy Research Institute, 2000)
This paper presents a new methodological framework for measuring the level of household access to credit. It provides an analytical framework for examining the determinants of household credit limits and derives implications on information needed to examine the extent to which households are credit constrained. Empirical application of this method involves directly eliciting credit limit information in household surveys. Illustrations are provided using data from Bangladesh and Malawi.